Measuring the Consistency of Pancasila Rule of Law Implementation in Ensuring Judicial Independence in Indonesia - Adies Kadir; Gunarto Gunarto; Abdullah Al-Monzur Hussain; Mohammad Abu Taher (Jurnal Hukum, 2025)
This study examines the consistency of the implementation of the Pancasila State of Law in guaranteeing judicial freedom in Indonesia, as stipulated in Article 1 paragraph (3) and Article 24 paragraph (1) of the 1945 Constitution. The Pancasila State of Law integrates the rule of law, protection of human rights, the principles of legality, and judicial independence with Pancasila values that are philosophical, ethical, and religious. Judicial independence, as a key pillar, requires judges to be free from external intervention to produce fair and objective decisions. However, its implementation faces challenges, such as a history of executive intervention, the quality of human resources, and corrupt practices, collusion, and nepotism. This study uses a juridical normative method, analyzes laws and regulations, legal doctrine, and judicial practices in Indonesia, and compares them with the Dutch and United States judicial systems. The results show the need for legal reconstruction through strengthening the guarantee of the position of judge, transparent recruitment, separation of powers, independent budget management, and improving the appeal and cassation mechanisms. This reform will ensure an independent, professional, and integrity judiciary, in line with the values of Pancasila.